2014
DOI: 10.1186/1471-2466-14-94
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the tight junction protein occludin: effects on ventilation-induced lung injury and mechanisms of action

Abstract: BackgroundOccludin, a tight junction protein, plays an important role in maintaining the integrity of the lung epithelial barrier; however, its role in ventilation-induced lung injury has not been explored. Here, we measured the expression of occludin with different tidal volumes. Our study indicated that the level of occludin was significantly decreased and alveolar permeability was increased owing to acute lung injury.MethodsThirty healthy Wistar rats (15 female, 15 male) weighing 250–300 g, were randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 20 publications
1
38
1
1
Order By: Relevance
“…In addition, the higher levels of total proteins induced by LPS in BALF were also inhibited by PIC treatment. Furthermore, tight junction proteins serve as important components in keeping the permeability of the air-blood barrier, and are down-regulated in the lung during ALI (Herold et al, 2013;Liu et al, 2014). In our study, we also found that the expression of tight junction protein ZO-1 and occludin were significantly reduced in the LPS treatment group mice compared to that in the control groups mice.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, the higher levels of total proteins induced by LPS in BALF were also inhibited by PIC treatment. Furthermore, tight junction proteins serve as important components in keeping the permeability of the air-blood barrier, and are down-regulated in the lung during ALI (Herold et al, 2013;Liu et al, 2014). In our study, we also found that the expression of tight junction protein ZO-1 and occludin were significantly reduced in the LPS treatment group mice compared to that in the control groups mice.…”
Section: Discussionsupporting
confidence: 74%
“…Regarding connexin 43, the data in the literature are controversial. While some studies showed increased expression of connexin 43 following ALI/ARDS (21,26), others reported an absence of connexin 43 within a few days after exposure to endotoxin (17). Unlike VE-cadherin, claudin 18 and 5, and connexin 43, in our hands, occludin levels failed to show a sign of decline at early time points after exposure to ricin, their reduction being observed…”
Section: L264contrasting
confidence: 78%
“…only from 48 h postexposure onwards. Decreased levels of occludin were documented by others in ventilation-induced lung injury (21). Neutrophils are proposed to have an important role in mediating ALI/ARDS.…”
Section: L265mentioning
confidence: 82%
“…Consistent with a role in regulating paracellular permeability, decreased lung occludin has been associated with several conditions known to promote pulmonary edema, including exposure to environmental toxicants, ventilator induced lung injury (VILI) and chronic exposure to alcohol [6064]. Also, rats pretreated with a PKCα inhibitor (bisindolylmaleimide) were protected from VILI, which correlated with an increase in total lung occludin protein [65]. Whether diminished occludin expression associated with VILI has an effect on claudins was not determined nor was it determined whether occludin was necessary for protection from VILI.…”
Section: Claudin Structure and Composition In Tight Junctionsmentioning
confidence: 99%